In vitro pharmacological characterization of standard and new lysophosphatidic acid receptor antagonists using dynamic mass redistribution assay - Ruzza, C.; Argentieri, M.; Ferrari, F.; Armani, E.; Trevisani, M.; Marchini, G.; Calo’, G. (Frontiers in Pharmacology, 2023)
Lysophosphatidic acid (LPA) is a bioactive phospholipid that acts as agonist of 6 G protein coupled receptors named LPA receptors (LPA1-6). LPA elicits diverse intracellular events and modulates several biological functions including cell proliferation, migration, and invasion. Overactivation of the LPA-LPA receptors system is reported to be involved in several pathologies, including cancer, neuropathic pain, fibrotic diseases, atherosclerosis, and type 2 diabetes. Thus, LPA receptors modulators may be clinically relevant in numerous diseases, making the identification and pharmacodynamic characterization of new LPA receptors ligands of high interest. In the present work the label-free dynamic mass redistribution (DMR) assay has been used to evaluate the pharmacological activity of some LPA1 and LPA2 standard antagonists at the recombinant human LPA1 and LPA2 receptors. These results have been compared to those obtained in parallel experiments with the calcium mobilization assay. Additionally, the same experimental protocol has been used for the pharmacological characterization of the new compound CHI. KI 16425, RO 6842262, and BMS-986020 behaved as LPA1 inverse agonists in DMR experiments and as LPA1 antagonists in calcium mobilization assays. Amgen compound 35 behaved as an LPA2 antagonist, while Merck compound 20 from WO2012028243 was detected as LPA2 inverse agonist using the DMR test. Of note, for all the compounds, similar potency values were estimated in DMR and calcium assay. The new compound CHI resulted a LPA1 inverse agonist but with potency lower than the standard compounds. In conclusion, we demonstrated that the DMR assay can be successfully used to characterize LPA1 and LPA2 ligands. Compared to the classical calcium mobilization assay, DMR offers some advantages, in particular allowing the identification of inverse agonists. Finally, in the frame of this study, a new LPA1 inverse agonist has been identified.